From Divergent Paths to the Same Trap: The Legitimacy Crisis of the Investor-State Dispute Settlement System - Sönmez, Esma Yağmur (Middle East Technical University, 2024)
This thesis critically examines a much-debated issue in international law: the legitimacy of the Investor-State Dispute Settlement system (ISDS). The system was initially conceived to provide an alternate dispute resolution mechanism for the protection and promotion of foreign investment. In time, this objective has incited a discussion on the legitimacy of the system as the developed world has started to experience the role of host states. Since then, they have taken the lead in the reform process to achieve a balance between host state's and foreign investors' rights. To this effect, both the European Union (EU) and the Third Way Approaches to International Law (TWAIL) are for centralization of the system arguing its current problems emanate from its ad hoc and decentralized nature. Although both are aimed at system centralization, the paths they take to achieve it clearly differ. The EU seeks a permanent investment court by which ad hoc arbitration would give way to a more centralized framework. However, TWAIL advocates for a return to the pre-ISDS era, where national courts resolve investment disputes between foreign investors and states. The effectiveness of these two reform ideas in addressing the purported legitimacy concerns of the ISDS is critically examined in this thesis using Martti Koskenniemi's legal approach. Ultimately, it asserts that neither proposal is adequate to resolve the legitimacy issue of the system, as legitimacy can only be achieved by strengthening the principle of justice, which is feasible alone through a more decentralized structure.
Keywords: ADR; Alternative dispute resolution; Foreign investment; Foreign investors; ISDS; Investment Dispute; Investments; Investor-State Dispute Settlement

Essai sur les critères d'arbitrabilité des litiges en Droit OHADA et en Droit Français - Dizo, Kevin (Nantes Université, 2024)
Le sujet de thèse explore comment définir les critères d’arbitrabilité des litiges acceptés par la justice arbitrale et étatique en France et dans l’espace OHADA. Les recherches ont montré que chaque système juridique a déjà des critères établis par les législateurs et la doctrine. L’arbitrage, étant à la fois juridictionnel et conventionnel, implique une interaction entre les justices arbitrales et étatiques, nécessitant des critères d’arbitrabilité efficaces. Ces critères doivent distinguer clairement les litiges arbitrables des inarbitrables et repartir soigneusement les compétences entre les juridictions. Alors, notre thèse questionne l’efficacité de ces critères et propose des améliorations pour remédier à leurs limites. The thesis topic explores how to define the arbitrability criteria of disputes accepted by arbitration and state justice in France and in the OHADA space. Research has shown that every legal system already has criteria set by legislators and doctrine. Arbitration, being both jurisdictional and conventional, involves an interaction between the arbitral and state courts, requiring effective arbitrability criteria. These criteria must clearly distinguish between arbitrable and non-arbitrable disputes and carefully allocate jurisdiction between the courts. So, our thesis questions the effectiveness of these criteria and proposes improvements to remedy their limitations.
Keywords: Arbitrability; Arbitrabilité; Arbitrage (droit); Arbitration; Criteria; Critères; Droit prospectif; Effectiveness; Efficacité; Pays de l'OHADA; Prospective law

Favoriser la culture du règlement amiable des différends : étude du droit béninois à la lumière du droit français - Ligan, Cyrille Sèmako (Université de Limoges, 2024)
Cette réflexion se propose de contribuer au développement des modes amiables de règlement des différends dans la culture juridique béninoise afin de permettre aux justiciables, majoritairement analphabètes, d'avoir des alternatives opportunes aux voies judiciaires classiques. Tandis que la justice fait face à de nombreux défis, aussi bien en France qu'au Bénin, le développement et la promotion remarqués des modes amiables de règlement des différends connaissent un certain succès en la matière en France. Au Bénin, le législateur encourage, incite mais ne propose aucun régime particulier pour le recours effectif au règlement amiable des différends. Cette recherche tente ainsi d'examiner de façon approfondie et d'interroger les différends mécanismes législatifs existants, tant les enjeux en termes d'accès à la justice sont considérables. Les principaux enjeux de cette thèse sont donc liées aux perspectives du développement des mode amiables et à leur encadrement pour remédier aux insuffisances et contre-performances de la justice étatique béninoise.
Keywords: Amicable settlement; Bénin / OHADA; Civil Procedure; Culture; France; Justice; MARD; Mediación; Mediation; Mediação; Médiation; Procédure civile; Règlement amiable

A renúncia a direitos fundamentais processuais na arbitragem: o caso particular do direito a requerer a anulação da sentença arbitral na arbitragem internacional - Teles, Joana Ataíde Cordeiro Galvão (Universidade Nova de Lisboa, 2024)
A arbitragem é um meio de resolução de litígios, que se alicerça na autonomia privada e é reconhecida, quer internacionalmente, quer nas constituições estaduais analisadas, como um modo de exercício, alternativo aos tribunais estaduais, do direito fundamental constitucional à tutela jurisdicional efetiva. A questão que se coloca é a de saber se, em primeiro lugar, as partes podem acordar renunciar, validamente, a direitos fundamentais processuais na arbitragem e, podendo, com que requisitos e dentro de que limites, para, em segundo lugar e em particular, aplicar os requisitos e limites referidos à (in)admissibilidade da renúncia ao direito a requerer a anulação da sentença arbitral na arbitragem internacional. Partindo da ponderação do âmbito, conteúdo e regime dos direitos fundamentais em confronto, de um lado, à tutela jurisdicional efetiva, incluindo o direito à arbitragem e outros direitos fundamentais processuais, como o de impugnar a sentença arbitral em determinados casos e, do outro lado, à autonomia privada, que fundamenta a renúncia, e sem prejuízo de a ponderação dever ser feita em cada caso concreto, concluo que a renúncia àqueles direitos é válida, se cumprir determinados requisitos subjetivos e objetivos, que identifico, incluindo os limites e os respetivos critérios para aferir da referida (in)validade. Quanto ao direito a requerer a anulação da sentença arbitral na arbitragem internacional, concluo que, sem prejuízo e com base nas soluções consagradas de jure constituto, a renúncia por acordo das partes é, do ponto de vista constitucional normativo e, de jure constituendo no direito português, válida, desde que se respeitem aqueles requisitos. Em particular, tem de existir um meio de impugnar a sentença arbitral, quando esta viole, de forma grave, direitos fundamentais processuais e/ou interesses de ordem pública de cada Estado, que não estão na disponibilidade das partes, nos casos e termos necessários a garantir o conteúdo essencial do direito fundamental à tutela jurisdicional efetiva. No entanto, há margem do legislador para adotar o regime mais adequado ao propósito referido. Na arbitragem internacional, do ponto de vista normativo-constitucional, podem as partes renunciar, total e/ou parcialmente, à anulação na sede, quando há a possibilidade de controlo último, pelo menos de violações graves de direitos fundamentais processuais e/ou interesses de ordem pública de cada Estado, aquando do reconhecimento e execução da sentença arbitral, sendo esta a solução legal que, na minha opinião, melhor se coaduna com a arbitragem internacional no seu todo. Arbitration is a dispute resolution mechanism rooted in private autonomy and internationally recognised, as well as in the national constitutions analysed, as an alternative means to state courts for exercising the constitutional fundamental right to effective judicial protection. The primary question of this dissertation is whether the parties can validly agree to waive fundamental procedural rights in arbitration, and if so, under what conditions and within what limits. Secondly, I specifically apply these conditions and limits to the (in)admissibility of waiving the right to seek annulment of the arbitral award in international arbitration. By weighing the scope, content and framework of conflicting fundamental rights – the right to effective judicial protection (encompassing the right to arbitration and other fundamental procedural rights, such as the right to challenge the arbitral award in certain cases), against private autonomy (which justifies the waiver) – and, without prejudice to the necessary case-by-case balancing, I conclude that the waiver of these rights is valid, provided that subjective and objective requirements, including the limits and criteria for assessing the (in)validity of the waiver, are met. Regarding the right to request annulment of the arbitral award in international arbitration, I conclude that, without prejudice to and relying on legal solutions established de jure constituto, the waiver by agreement of the parties is valid from a normative constitutional perspective and de jure constituendo under Portuguese Law, provided such subjective and objective requirements are respected. Specifically, there must be a means to challenge the arbitral award when it seriously violates fundamental procedural rights and/or public order interests of each State, which are beyond the parties’ disposal, in certain cases and under certain terms as necessary to protect the core essence of the fundamental right to effective judicial protection. However, the legislator retains discretion to adopt the most appropriate legal framework for this purpose. In the context of international arbitration, from a normative-constitutional perspective, the parties may waive annulment at the seat, in whole and/or in part, provided there is the possibility of ultimate oversight, particularly in cases involving serious violations of fundamental procedural rights and/or public order interests of each State at the stage of recognition and enforcement of the arbitral award. In my opinion, this legal solution is the one that best aligns with the global system of international arbitration.
Keywords: Annulment; Anulação; Arbitragem; Arbitragem Internacional; Arbitration; Autonomia Privada; Direitos Fundamentais Processuais; Fundamental Procedural Rights; International Arbitration; Private Autonomy; Renúncia; Waiver

Procedural Justice in Online Dispute Resolution: An Empirical Enquiry - Beretta, Rachele (University of Antwerp, 2024)
The surge in online interactions has led to a parallel rise in civil and commercial disputes that transcend geographical boundaries. As traditional dispute resolution mechanisms face challenges adapting to this evolving paradigm, conflicts increasingly migrate to online platforms. Within this proliferating landscape, it is crucial to recognize the scarcity of research devoted to Online Dispute Resolution (ODR) providers and the myriad types of services they currently offer to users worldwide. Despite the ongoing geographical expansion of ODR, the inquiry into how procedural justice principles manifest in these digital dispute resolution systems remains notably under-explored. A growing body of literature underscores that procedural justice is critical for building users’ trust, enhancing the legitimacy of organizations among communities, and fostering compliance with outcomes. The ability of ODR providers to meet users' expectations in terms of procedural justice can significantly shape users' perception of ODR institutions as trustworthy and dependable. This bears paramount implications for the ongoing development of ODR, whose acceptance varies widely across jurisdictions. This doctoral thesis delves into the intricate intersections of procedural justice within the realm of international civil and commercial ODR, examining the nuanced dynamics that emerge in virtual spaces. Ultimately, it seeks to understand how procedural justice principles, rooted in the notion of fairness, manifest and evolve in the context of ODR, exploring the impact of digital interventions on the perceived fairness of dispute resolution processes. Understanding procedural justice in ODR is not merely an academic pursuit; it holds profound implications for legal practitioners, policymakers, and society at large. This research aims to contribute valuable insights that can inform the design of fairer and more effective ODR systems.
Keywords: Dispute Settlement; Justice; ODR; Online Dispute Resolution; Procedure (Law); UNCITRAL Arbitration Rules

Bireysel iş uyuşmazlıkları bakımından dava şartı arabuluculukta taraflar - Güngör, Tuba (Kırıkkale Üniversitesi, 2024)
Türk hukukunda, özellikle iş uyuşmazlıkları bakımından arabuluculuğun dava şartı olarak kabul edildiği tarihten bu yana, arabuluculuk kurumundan beklenen faydanın elde edilip edilmediği bir yana bırakılırsa öğreti ve uygulamada halen tartışıla gelen birçok konu bulunmaktadır. Bunlardan biri, çalışma konumuzu oluşturan bireysel iş uyuşmazlıkları bakımından dava şartı arabuluculukta işçi ve işveren tarafların doğru ve tam olarak teşkilinin sağlanmasıdır. Alternatif çözüm yollarından biri olan arabuluculuğun dava şartı olarak düzenlenmesi, arabuluculuk faaliyetini yargılamanın ön şartı ve ayrılmaz bir parçası haline getirmiştir. Bu bakımdan arabuluculuk sürecinin doğru işçi veya işveren tarafla yürütülmemesi yargılamayı doğrudan etkileyecektir. İş uyuşmazlıkları bakımından işçi sıfatının belirlenmesi özellikle işçi olup olmadığı konusunda tereddüt yaşanan çalışanlar açısından önemlidir. İşveren tarafının doğru belirlenmesi ise, arabuluculuk faaliyetinin yanlış veya eksik işverenle yürütülmesinin ardından, yargılama sürecinde bu durumun tespit edilmesi halinde işveren tarafında değişiklik yapılamaması bakımından önem arz etmektedir. Arabuluculuk dava şartı olarak düzenlendiğinden, yargılama sırasında tamamlanabilmesi olanaklı değildir. Sürecin bu şekilde işlemesi ise mahkemeye erişim hakkının önünde engel teşkil edebileceği gibi, gerek iş güvencesi gerekse işçinin alacağına kavuşma noktasında hak kaybına ve mağduriyetine yol açabilecektir. In Turkish law, especially since the adoption of mediation as a condition for litigation in terms of labour disputes, there are still many issues that are still debated in the doctrine and practice, let alone whether the expected benefit of the mediation institution has been achieved. One of these issues is to ensure that the employee and employer parties are accurately and fully constituted in the mediation as a condition for litigation in terms of individual labour disputes, which is the subject of our study. The regulation of mediation as a condition of litigation, which is one of the alternative remedies, has made the mediation activity a prerequisite and an integral part of the proceedings. In this respect, failure to conduct the mediation process with the right employee or employer party will directly affect the proceedings. In terms of labour disputes, the determination of the employee party is especially important for employees who are in doubt as to whether they are employees or not. The correct determination of the employer party is important in terms of not being able to make changes on the employer side if this situation is detected during the proceedings after the mediation is carried out with the wrong or incomplete employer. Since mediation is regulated as a condition of litigation, it is not possible to complete it during the proceedings. This process may constitute an obstacle to the right of access to the court, and may lead to loss of rights and victimisation in terms of both job security and the employee's receivables.
Keywords: Dava şartı arabuluculuk; Employee; Employer; Iş uyuşmazlığı; Işveren; Labour dispute; Mediation; İşçi

Arabuluculuk faaliyetinin anlaşma ile sona ermesi - Terzi̇ Kahraman, Si̇bel (Kadir Has Üniversitesi, 2024)
Arabuluculuk kurumundan beklenen avantajların ortaya çıkabilmesi arabuluculuk faaliyeti sonunda anlaşmaya varılması ile mümkündür. Mevzuatta sürekli değişiklikler meydana gelmekte ve kurumun kapsamına aldığı uyuşmazlıklar hızla genişletmektedir. Uygulamanın yerleşmesi ve zaman zaman doktrinde görüş ayrılıkları yaşanması kaçınılmazdır. Mevzuatta daha detaylı ya da değiştirilerek düzenlenmesine ihtiyaç duyulan alanlar bulunmaktadır. Tez, mevzuatta yapılan son düzenlemeleri de kapsayarak anlaşmayı tüm yönleriyle ele almayı ve kurumun daha iyi anlaşılmasına hizmet etmeyi amaçlamaktadır. Yapılan bu çalışmanın ilk bölümde arabuluculuğun kurumsal çerçevesi ortaya konulmuştur. Bu bölümde amaç arabuluculuk kurumunu ve arabuluculuk faaliyetinin işleyişini anlatabilmektir. Bu amaçla arabuluculuğun kapsamı, türleri, arabuluculuğun karşılaştırmalı hukukta ve Türk hukukunda gelişimi, yargı ve tahkimden farkı, med-arb uygulaması anlatılmıştır. İkinci bölümde sona erme halleri tek tek ele alınmış, sona erme hallerinin mevzuatta dağınık halde düzenlendiği hususuna dikkat çekilmiş ve başkaca sona erme halleri de dikkate alınarak tek bir madde halinde düzenlenebilmesi hususu önerilmiştir. Arabulucunun, faaliyeti sona erdirme yönünde inisiyatif almasının sona erme hali olarak düzenlenmesi yönünde de öneri getirilmiştir. Üçüncü bölümde anlaşmanın terminoloji sorununa ve benzer kavramlardan farkına değinilmiştir. Arabuluculuk faaliyeti sonunda varılan anlaşmanın esaslı unsurları tespit edilmiştir. Bu kapsamda, sözleşme serbestisi, şarta bağlı edim düzenlenip düzenlenemeyeceği gibi önemli hususlara yer verilmiştir. Anlaşmanın nasıl düzenleneceğine ilişkin öneride bulunulmuştur. Anlaşmanın hukuki niteliği, anlaşılan hususlara karşı dava açılamayacağı, anlaşmanın hukuka uygun düzenlenmediği takdirde karşılaşılabilecek sonuçlar anlatılmış ve anlaşmanın arabuluculuğa elverişli olmamasına rağmen düzenlenmesi, dava şartı kapsamına girmeyen bir hususta faaliyetin yürütülmesi ve anlaşmaya varılması, yanlış dava türünden yapılan başvuru sonucu anlaşmaya varılması, arabulucunun uzmanlık alanına girmeyen bir konuyla ilgili anlaşma sürecini tamamlaması, hukuka uygun arabuluculuk faaliyeti yürütülmemesi sonucunda anlaşmaya varılması, arabulucunun arabuluculuktan çekilmesi gerekirken yine de anlaşma yapması gibi anlaşmadan kaynaklı sorunlara yer verilmiştir. Dördüncü bölümde anlaşmanın yerine getirilmemesi durumunda icra edilebilirlik şerhi alınması hususu, mahkemeye başvuru, yargılama usulü, mahkemenin incelemesi, şarta bağlı olarak yapılan anlaşmaya şerh verilmesi, icra edilebilirlik şerhi alınan anlaşmanın icrası, anlaşmayla ilamlı ve ilamsız takip yapılması gibi önemli hususlar ele alınmıştır. Son olarak, arabuluculuk sonucunda elde edilen uluslararası ticari anlaşmaların icra edilmesini kolaylaştırması amacıyla hukukumuzda da kabul edilen Singapur Konvansiyonu incelenmiştir. The expected advantages of the mediation institution can be realized through reaching an agreement at the end of the mediation process. There are continuous changes in the legislation, rapidly expanding the scope of disputes covered by the institution. The thesis aims to comprehensively examine the agreement reached at the end of the mediation process, including recent legislative amendments, to better understand the institution and its operations. The first part of this study outlines the institutional framework of mediation, explaining its scope, types, development in comparative law and Turkish law, differences from judiciary and arbitration, and the practice of med-arb. The second part discusses the various termination conditions, highlighting the scattered nature of these conditions in legislation and proposing their consolidation into a single provision. It also suggests granting mediators the initiative to terminate the process as a termination condition. In the third part, attention is given to the terminology issues and distinctions from similar concepts regarding the agreement reached through mediation. The essential elements of such agreements are identified, covering issues like contractual freedom and the regulation of conditional obligations. Recommendations are made on how agreements should be drafted. The legal nature of the agreement, restrictions on litigation concerning agreed-upon matters, consequences of improperly drafted agreements, and issues arising from inappropriate mediation activities are discussed. The fourth part addresses the issue of obtaining enforceability endorsements for agreements not fulfilled, court applications, trial procedures, court reviews, endorsement of conditional agreements, enforcement of endorsed agreements, and procedures for enforcement with and without judgments. Finally, the study explores the Singapore Convention, adopted in our legal system to facilitate the enforcement of international commercial agreements resulting from mediation.
Keywords: ADR; Agreement termination; Alternative dispute resolution; Anlaşmazlık; Arabuluculuk; Executability Annotation; Kanunlar 6325 sayılı; Laws 6325 numbered; Mandatory mediation; Mediation; Mediator; Médiation; Singapore Convention; Zorunlu arabuluculuk

Sermaye şirketlerinde zorunlu arabuluculuk - Ulusan, Banu (Galatasaray Üniversitesi, 2024)
Çalışma 06.12.2018 tarihinde 7155 sayılı Kanun ile Türk Ticaret Kanunu'na eklenen TTK m. 5A hükmüyle getirilmiş zorunlu arabuluculuğun, sermaye şirketleri çerçevesinde incelenmesini konu almaktadır. TTK m. 5A hükmüyle önce, ticari davalardan, konusu bir miktar paranın ödenmesi olan, alacak ve tazminat davalarının zorunlu arabuluculuğa tabi olduğu düzenlenmiştir. Daha sonra, 28.02.2023 tarihli ve 7445 sayılı Kanun ile yine ticari dava olmaları kaydıyla, menfi tespit, itirazın iptâlî ve istirdat davalarını da zorunlu arabuluculuk kapsamına almıştır. TTK lafzıyla dava şartı arabuluculuk olarak da nitelendirilen zorunlu arabuluculuk kavramı, Türk hukuku bakımından yeni bir kavram sayılabilir. İlk olarak 2017 yılında 7036 sayılı Kanun ile iş uyuşmazlıkları için düzenlenen zorunlu arabuluculuk kavramı, daha sonra ticari uyuşmazlıklar ve tüketici uyuşmazlıkları için de düzenlenmiştir ve Türk hukukunda zorunlu arabuluculuğun uygulama alanı git gide genişleme eğilimi göstermektedir. Bu sebeple, doktrinde pek çok eleştiriye de uğrayan zorunlu arabuluculuk kavramının, özellikle sermaye şirketleri bağlamında incelenmesi amaçlanmıştır. Her ne kadar Türk hukukunda yeni bir kavram olsa da, karşılaştırmalı hukukta zorunlu arabuluculuk uzun zamandan beri uygulanan ve tartışilânbir konu olagelmiştir. Karşılaştırmalı hukuk bağlamında bir inceleme yapıldığında öncelikle, özellikle zorunlu arabuluculuğun menşei sayılabilecek Amerikan hukukunda, konu özellikle doktrinde farklı açılardan ele alınmıştır. Çalışmanın birinci bölümünde bu çerçevede bir inceleme yapılmış, zorunlu arabuluculuğun tabi olması gereken kıstaslar ortaya konulmaya çalışılmıştır. Bu kıstaslar, çalışmanın ilerleyen bölümlerinde yapılacak değerlendirmeler için de önem taşımaktadır. Bunun yanı sıra zorunlu arabuluculuğun türleri ve zorunlu arabuluculuğa aykırı davranışlara bağlanan yaptırımlar üzerinde de durulmuştur. Zorunlu arabuluculuğun ve benzeri uygulamaların farklı hukuk sistemlerinde ne şekilde yer aldığı değerlendirilmiştir. Bu değerlendirmeler kapsamında Alman hukuku bakımından ZPO §278 ile EGZPO §15a incelenmiştir. İsviçre hukuku bakımından ise ZPO §197 vd. hükümleri incelenmiştir. Her iki hukuk sistemi de zorunlu arabuluculuğu düzenlememiş, bunun yerine medeni usûl kanunlarında davanın görüleceği mahkemeler nezdinde uyuşmazlık çözüm sürecini düzenlemiştir. İtalya ve Fransa'da ise zorunlu arabuluculuk uygulamaları mevcut ise de bu, Türk hukukunun aksine, son derece sınırlı bir şekilde gerçekleşmiştir. Zorunlu arabuluculuğun kaynağı olan Amerikan hukukunda ise arabuluculuk, zorunlu tutulan tek uyuşmazlık çözüm yöntemi olmamıştır. Ayrıca zorunluluk hususu kanunla değil, genellikle her bir dava için mahkemenin yönlendirmesiyle sağlanmaktadır. Tüm bu ülkelerin ortak özelliği ise ticari uyuşmazlıkları zorunlu arabuluculuğa ya hiç tabi tutmamaları ya da çok dar bir kapsamda tabi tutmalarıdır. Arabuluculuk her ne kadar bir yargılama faaliyeti olmasa da zorunlu arabuluculuk dava öncesinde yer alan bir aşama olduğundan, kanaatimizce medeni usûl hukukuna hâkim olan ilkeler bakımından da incelenmelidir. Bu kapsamda zorunlu arabuluculuğun öncelikle adil yargılanma ilkesi ve mahkemeye erişim hakkı kapsamında tartışmalara sebep olduğu görülmektedir. Bunun yanı sıra usûl ekonomisi ilkesi, aleniyet ilkesi, tasarruf ilkesi ve dürüst davranma yükümlülüğü bakımından da değerlendirmelere yer verilmiştir. Aleniyet ilkesi bağlamında arabuluculuğa hâkim olan ilkelerden gizlilik ilkesinin ticari uyuşmazlıklar bakımından bir avantaj oluşturduğu söylenebilir. Tasarruf ilkesinde yapılandeğerlendirme maddî hukuk ve usûl hukuku çerçevelerinde yapılmıştır. Ayrıca zorunlu arabuluculuğun menşei Amerikan hukukunda hâkimin ve avukatların rolleri de dikkate alınarak, zorunlu arabuluculuğun Türk hukukundaki hâkimin yargılamayı sevk ve idaresi ilkesiyle tamamen bağdaşmadığı sonucuna varılmıştır. Dürüstlük ilkesi bakımından yine maddî hukukla da bağlantı kurularak bir değerlendirme yapılmış, zorunlu arabuluculuk süreci sonunda varılacak anlaşmanın dürüstlük kuralına uygun yapılması için yeterli mekanizmaların bulunmadığı kanaatine varılmıştır. Bunun dışında HUAK m. 18A/11 hükmü uyarınca zorunlu arabuluculuk sürecinin ilk toplantısına mazeretsiz katılmayan tarafın her durumda yargılama giderlerinin tümünden sorumlu olması ve lehine vekalet ücretine hükmedilememesinin orantısız bir yaptırım olduğu, ayrıca bu sebeple hiçbir durumda yargılama giderlerinden sorumlu olmayacağını bilen tarafın, açılacak dava sürecinde davayı uzatacak veya yanlış yönlendirecek ve dürüstlük kuralına uymayacak her tür davranışı yapabileceği kanaatine varılmıştır. Çalışmanın ikinci bölümü TTK m. 5A hükmünün uygulama koşullarına yoğunlaşmaktadır. Bu kapsamda, ticari davalar bakımından karşılaştırmalı bir değerlendirme yapılmak istenmiştir. Türk hukukunda TTK m. 4 hükmüyle ayrıca düzenlenen ticari davalar, diğer hukuk sistemlerinde ticaret mahkemeleriyle ilişkili olarak düzenlenmiştir. Bu değerlendirmede dikkat çeken husus, davaların ucuz, hızlı ve etkin bir şekilde sonuçlandırılmasının amaçlandığı diğer hukuk sistemlerinde hukukçu olmayan hâkimlerin de görev yaptığıdır. Türk doktrininde ise böyle bir uygulamanın uygun olmayacağı haklı olarak belirtilmiş, bu bağlamda zorunlu arabuluculuk uygulamasının daha uygun olduğu kanaatine varılmıştır. Ticari davalarda dava şartını düzenleyen TTK m. 5A hem medeni usûl hukuku hem de ticaret hukuku bakımından incelenmiştir. Medeni usûl hukukun bakımından yapılanincelemede dava şartı kavramı ve hükmün dava türlerine göre gösterdiği özellikler incelenmiştir. Ticaret hukuku bakımından ise, arabuluculuk süreci sonucunda varılacak anlaşmanın bir maddî hukuk sözleşmesi oluşundan da yola çıkarak basiretli tacir kavramı incelenmiştir. Ayrıca zorunlu arabuluculuğun HUAK m. 5 hükmü ve gizlilik ilkesi nedeniyle göstereceği özellikler nedeniyle, ticari sırların korunması bağlamında da bir değerlendirme yapılmıştır. Çalışmanın üçüncü ve son kısmı sermaye şirketlerinde zorunlu arabuluculuğun incelenmesine ayrılmıştır. Bunun için öncelikle Alman hukukunda pay sahipleri davaları olarak adlandırilândavalar hakkında değerlendirme yapılmaya çalışılmıştır. Bu değerlendirmeyle adi şirketlerden farklı olarak pay sahipleri davalarının genel olarak ortağa değil şirket tüzel kişiliğine yöneltilmesi gerektiği, bunun yanı sıra pay sahiplerinin şirketin menfaatleri için dava haklarını kullanabildiği görülmüştür. Bu değerlendirmenin, sermaye şirketleri uyuşmazlıklarında zorunlu arabuluculuk sürecinde başvuru yapacak taraflar ve anlaşmanın etkileyeceği kişilerin tespitinde yararlı olduğu kanaatindeyiz. Bu değerlendirmenin ardından TTK m. 5A kapsamına girebilecek sermaye şirketi uyuşmazlıkları tespit edilerek, her biri için zorunlu arabuluculuğun göstereceği özelliklerin belirlenmesine çalışılmıştır. Bu belirleme yapılırken her bir uyuşmazlık konusu hakkında genel bir çerçeve sunulmuş, açılabilecek davalar hakkında bilgi verilmiş ve bu bilgiler ışığında zorunlu arabuluculuğun uygulama koşulları ile doğurabileceği sakıncalar üzerinde durulmuştur. Son olarak, yapılantüm değerlendirmeler ışığında sermaye şirketlerinde zorunlu arabuluculukla ilgili de lege ferenda görüşümüze yer verilmiştir. Bu kapsamda sermaye şirketleri uyuşmazlıklarının, dava konularının şirketler hukuku kısıtlarına ve emredici kurallara tabi olması sebebiyle, zorunlu arabuluculuğa her zaman uyumlu olmayabileceği sonucuna varılmıştır. Üstelik, bazı arabuluculuk türlerinde yapılması elzem hukuki denetimin ve arabulucunun bu denetimi yapamayacak olmasının yaratacağı sakıncalara da değinilmiştir. Bunun sonucunda İsviçre ve Almanya örneklerinde olduğu gibi mahkeme bağlantılı uyuşmazlık çözümlerinin düzenlenmesinin daha uygun olduğu kanaatine varılmıştır. İflas bakımından bir değerlendirme yapıldığında ise, İİK m. 226 hükmü nedeniyle doğabilecek sorunlara dikkat çekilmiş, bu bağlamda zorunlu arabuluculuğa başvuru kapsamında düzenleme yapılması önerilmiştir. Son olarak zorunlu arabuluculuk ile varılmak istenen amaçlar da dikkate alındığında, bu amaçlara ulaşmak için taraflara arabuluculuk dışında uyuşmazlık çözüm yollarına başvurabilmelerine imkân verilmesi gerektiği kanaatine varılmıştır. Bu şekilde hem çabuk ve ucuz bir şekilde uyuşmazlıkların çözümü amacına ulaşabilecek, hem de tarafların ihtiyaçlarına daha uygun bir yöntem seçmelerine imkân tanınacaktır. […] This study focuses on application of Turkish Commercial Code Art. 5A, which is amended with Code Nr. 7155 in 2018, to equity companies. TCC Art. 5A regulated mandatory mediation for commercial cases with monetary claims at the beginning. However, through amendment with Code Nr. 7445 in 2023, negative declaratory actions, actions for annulment of objections and actions for restitution were taken into scope of this regulation. Mandatory mediation, which can also be named mediation as cause of action according to TCC m. 5A, can be deemed as a new context in Turkish law. Regulated for the first time for some labour law conflicts with Code Nr. 7036 in 2017, mandatory mediation is regulated also for commercial conflicts as well as consumer law conflicts. Thus, it can be observed that scope of mandatory mediation in Turkish law has a tendency to spread within time. Therefore, as a concept subject to various critics, mandatory mediation is to be evaluated in context of equity companies within this study. Although mandatory mediation is considered to be a relatively new concept in Turkish law, in frame of comparative law, it has a long history of application and has been subject to critics for a long time. It is observed that in comparative law, especially in American law, which can be considered as the source, mandatory mediation has been taken into consideration with many aspects. The first chapter of this study conducts an evaluation within this frame and aims to set the criterias for a better application of mandatory mediation. These criterias are important for evaluation in following chapters of this study. In addition, the variations of mandatory mediations and sanctions applied to the acts contrary to mandatory mediations are observed. Mandatory mediation and similar applications in different law systems are also examined. Within light of this examination, ZPO §278 and EGZPO §15a in German law is taken into consideration, as well as ZPO §197 ff. in Swiss law. Both systems do not regulate mandatory mediation and instead, regulated dispute resolution process within their Civil Procedure Codes. Although mandatory mediation is regulated in Itâlîan and French law systems, these regulations have strictly limited scope. American law, the origin of mandatory mediation, applies other means of dispute resolution as well. Moreover, mandatory mediation in American law is not regulated by a code; it is court oriented in general. The common point of these countries is that none of them applies mandatory mediation within a wide scope on commercial disputes. Although mediation cannot be considered as an act of judication, since mandatory mediation is a step before courts, it should be evaluated with regard of principals of civil procedure law. In this context, it is observed that mandatory mediation gave reason to many arguments related to fair trial and access to court. In addition, evaluations on principals pf procedural economy, publicity, power of disposition and honesty are conducted. With regard of principal of publicity, it can be considered that principal of confidentiality of mediation is an advantage. The evaluations on principal of power of disposition are made in frame of substantial and procedural law. Furthermore, taking the features of American civil procedure law, it is concluded that mandatory mediation is not compatible with the role of judge in Turkish law. With regard of principal of honesty, an evaluation in the light of substantial law is also made and it is concluded that rules to maintain honesty in mandatory mediation are not sufficient in Turkish law. As an addition, it is also stated that sanction in Code of Mediation Art. 18A/11 is unproportionate in context of principal of honesty before courts. The second chapter of this study focuses on conditions of TCC Art. 5A. With this regard, a comparative evaluation on commercial actions is made. Commercial actions, regulated with TCC Art. 4 in Turkish law, are regulated in relation with commercial courts in other law systems. With this evaluation, it is noted that in commercial courts, which aims to solve disputes in a cheap, quick and effective manner, gives place to judges who have not a judicial notion in other law systems. In Turkish literature, it is rightly emphasized that such an application is not appropriate for Turkish law. TCC Art. 5A is also examined within frame of civil procedure and commercial law. Within civil procedure law frame, the concept of cause of action is examined, as well as features of TCC Art 5A in relation to claim in actions. Within commercial law frame, since the agreement concluded within mediation is a contract in context of substantial law, the notion of prudent merchant is evaluated. Furtermore, for mandatory mediation demonstrates features within light of Code of Mediation Art. 5 and principal of confidentiality, an evaluation of trade secrets are also conducted. The third and last chapter concentrates on examination of mediation as a cause of action in equity company disputes. Thus, an action named shareholders' action in German law, which is clarified using notion of actio pro socio, is evaluated. According to this evaluation it is concluded that, unlike simple partnerships, shareholders shall submit their claims against legal entity of equity companies and not against other shareholders. Neverthless, it is also observed that in some cases shareholders are entitled to submit the tools of defence of equity companies for interests of company. This evaluation is essential in order to determine the parties of dispute and the persons effected from the agreement reached at the end of mandatory mediation process. Following this evaluation, the kinds of disputes in equity companies, which fall into scope of TCC Art. 5A, are determined and the features demonstrated by them in context of mediation as a cause of action are defined. In order to comply with this evaluation, information on each subject of action is given, features of the relevant actions are explained and in the light of all evaluations, conditions of application of mediation as a cause of action are explained. Finally, in light of evaluations made within this study, our de lege ferenda opinions on mandatory mediation in equity companies are set. Within this frame, since dispute in equity companies are subject to limitations on equity company law and compulsory legal rules, it is stated that they might not always compatible with mediation as a cause of action. In addition, possible problems arisen from lack of legal supervision in mediation process are also mentioned. As a result, it is concluded that, it would be more convenient to regulate court annexed dispute resolution tools, similar with examples of Germany and Switzerland. With regard to bankruptcy proceedings, it is concluded that possible problems in relation to Turkish Code of Bankruptcy and Enforcement Art. 226 are highlighted and it is suggested that, in order to eliminate such problems, necesarry regulations by legislator should be made. Lastly, taking the goals of mediation into consideration, in order to reach these goals effectively, the importance of giving parties the opportunity to be able to choose other means of dispute resolution apart from mandatory mediation, is found to be essential. Thus, dispute resolution process will take place in a quick and cheap manner and parties will have the chance to be able to choose a dispute resolution method that suits their needs and interests.
Keywords: MARD; Mediación; Mediation; Mediação; Médiation